2015
DOI: 10.2501/jar-55-2-216-227
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Direct Context As Revealed by Eye Tracking

Abstract: Many previous studies on attention have ignored the eye-catching potential of "direct context"-the entire promotional and editorial content an observer can view at the same time-in print media. In the current study, characteristics of 183 magazine advertisements and their direct context were coded systematically and linked to eye-tracking data, producing more than 19,000 observations. Expanding on earlier research, the authors focused on fixations within an advertisement during the first five seconds and atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Finally, size is considered a ‘powerful’ feature since marketing eye tracking research found that the larger the advertisement, the more attention the viewer paid to it [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, size is considered a ‘powerful’ feature since marketing eye tracking research found that the larger the advertisement, the more attention the viewer paid to it [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Neurophysiological methods, such as eye tracking and EEG, offer more direct measures of attention when compared 352 to self-reports and provide marketers with a reliable tool to successfully distinguish between bottom-up and top-down attention in relation to marketing-relevant stimuli (Boerman, van Reijmersdal, and Neijens 2015;Pieters and Wedel 2007). An eye-tracking study found, for example, that for magazine advertisements the position that attracts the most attention is the bottom of the right-hand page, next to an article or illustration with limited colors (Smit, Boerman, and van Meurs 2015). In EEG research on advertising, occipital alpha activity has been related to attention processes, such as visual gating during the viewing of TV commercials (Rothschild et al 1986).…”
Section: Attentionmentioning
confidence: 99%
“…Additionally, a 2015 study by Boerman et al "investigate[d] the influence of different ways of disclosing brand placement on viewers' visual attention, the use of persuasion knowledge, and brand responses" (p. 196). Brand placement has caught the attention of many stakeholders (e.g., academics, policy makers) because brand placement can distract readers (Cain, 2011). Boerman et al's (2015 results indicated the combination of text and the brand logo was most effective in increasing brand recognition as logos alone were not enough to increase participants' recognition of brands attracting visual attention.…”
Section: Communicationmentioning
confidence: 99%